'Good' farm management employment: Emerging values in the contemporary Irish dairy sector. (March 2020) - Deming, Justine; Macken-Walsh, Áine; O'Brien, Bernadette; Kinsella, James
Highlights: Tradition of esteem in farm ownership, with farm employment less esteemed. Some employers are reflexive in consciously exposing the farm to new skills & people. Employees value decision-making discretion and employers' appreciation of them. Social recognition of employees' abilities by peers cemented 'good employee' status. Lack of formal rewards threatens attractiveness of farm employment long-term. Abstract: The number of Irish dairy farms with herds greater than 100 cows has increased from 4.5 % in 2005 to 23 % in 2016. The abolition of the dairy quota in 2015 has led to predictions that this trend will continue and that an additional 6000 people will be required to work on dairy farms by 2025. Ownership of farms is esteemed, with farm employment perceived as a poor second option, so it is necessary to identify possible routes towards creating 'good' farm employment relationships. This paper explores the social, cultural and economic values of employers and employees in the context of early experiences of farm employment in post-quota Ireland. Using narrative analysis, this study found that employees gained esteem and pride from acquiring managerial responsibilities and receiving recognition for their abilities and accomplishments from their employers. Greater social recognition of employ' abilities by peer groups and in networks (social capital) cemented 'good employee' status. Employers, in a context of unprecedented dairy production expansion, emphasised the need for and demonstrated changing of power structures to open up the farm to new forms of influence. However, employers' reflexivity in support of employment relationships was undermined overall by what the management literature calls a weak 'rewards system' for employees. Without the supportive scaffolding of a formalised rewards system, relational gestures of responsibility-devolution and employ' appreciation of employees may be insufficient to sustain quality farm management employment in the long term. Inevitably, this diminishes the attractiveness of farm employment, limiting the drawing of talent not only into farm employment but into associated capacity-building programmes.